ANALISIS KINERJA KEUANGAN KOPERASI SIMPAN PINJAM (KSP) MITRA SEJAHTERA ABADI PAKEM SLEMAN YOGYAKARTA - yulia evita wulandari (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this research is to analyze the financial performance of Cooperative Savings and Loans (KSP) of Mitra Sejahtera Abadi period 2012 up to 2016 based on Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 06 / Per / M.KUKM / V / 2006 using current ratio analysis, Total Debt to total assets, Net Profit Margin, Own Capital Rentability, Return On Assets (ROA). This research was conducted at Cooperative Savings and Loans Mitra Sejahtera Abadi, Pakem, Sleman, Yogyakarta. This research is descriptive. The data used are secondary data, ie data that has been in though in the form of Balance Sheet and Income Statement. The results show that the current ratio is said in the criteria is not good, Total Debt to Total Assets is said in the criteria is not good, Net Profit margin said in good criteria, Own Capital Rentability is good, Return On Asset can be said in criteria less good.